Dakwah Tathwir Melalui Pembangunan Ekonomi Kerakyatan Berbasis Lingkungan - Aliyudin, Aliyudin (Prophetica, 2009)
Tathwirs dawah one of it can thru do economy development. Development in Islamic included economic aspect, shall everlastingly base devotion to God swt, get justice, benefit that gets to orient the world and eternity. Islam gives to appreciate that mulya divides its people that can look after and empowering environmentally nature for prosperity, welfare, and its life happiness.Keywords:Tathwir, Pembangunan Ekonomi, Pembangunan Berbasis Lingkungan